THE STUDY OF THE RHEOLOGICAL BEHAVIOR AND THE OXIDATION STABILITY OF SOME COSMETIC EMULSIONS - MANEA, Adela; TAMAȘ, Andra; NIȚU, Sabina; PERJU, Delia (Studia Universitatis Babeș-Bolyai Chemia, 2021)
The paper presents the rheological behavior study of cosmetic emulsions as well as their oxidation stability. The influence of temperature and of the cooling rate was determined, as well as that of the active principles content on the rheological behavior, by setting the dependence between the shear stress τ and the shear rate <img id="equationview" title="This is the rendered form of the equation. You can not edit this directly. Right click will give you the option to save the image, and in most browsers you can drag the image onto your desktop or another program." src="https://latex.codecogs.com/svg.latex?%5Cdot%7B%5Cgamma%7D" name="equationview" />​. The analysis of this dependence demonstrates that these emulsions present non-Newtonian behavior. The oxidation stability was monitored for 210 days by determining the peroxide value and the presence of initial and final oxidation products (by monitoring K232 and K270 values, respectively).